Numerical investigation of direct absorption solar collectors (DASC), based on carbon-nanohorn nanofluids, for low temperature applications. (1st January 2020) - Simonetti, M.; Restagno, F.; Sani, E.; Noussan, M.
Highlights: Direct absorption solar collectors (DASC) with nanofluids are simulated by CFD. Nanofluid light absorption performance are experimentally measured. Simulated design does not fully exploit theoretical advantages of DASC. Optimization of DASC design is needed to foster their potential at low temperature. Abstract: Direct absorption solar collector (DASC) have recently attracted increasing interest in combination with some new absorbing fluids, obtained through the suspension of nanoparticles in water or other liquids (nanofluids). A volumetric direct absorption in a solar collector is in principle more convenient than a superficial indirect one, assuring a temperature distribution whose peak is internal to the fluid instead and not on the external surface, as in superficial one, thus promising lower heat losses. Nanofluids, i.e. fluids with a suspension of nanoparticles, such as the carbon nanohorns we choose as case study, can be considered a good and innovative family of absorbing fluids, due to their higher absorption coefficient than the pure base fluid and to their high stability under moderate temperature gradients. In this paper, we focus on the application of direct volumetric absorption by nanofluids for civil applications, which have a typical operative temperature lower than 100 °C. A DASC using nanofluids with different nanoparticle concentrations is compared to a commercially available indirect vacuum tube solar collector. The comparison is made between simulated performance of the DASC and the nominal performance of the commercial collector. The simulations are made with a CFD model, that leverages original experimental measurements of the optical properties of the considered nanofluid. It is shown that the DASC concept is more convenient in case of higher heat losses, i.e. in case of a high transmittance solar collector or of very high temperature of the heated fluid. It is also underlined the importance of balancing the heat absorption and heat transport function of the fluid. The simulations of the first considered design reveals, in fact, that the thermal field does not completely develop in the pipe, due to the large pipe diameter in relation to the flow and to the low heat losses, thus producing a low bulk temperature. The addition of a compound parabolic concentrator (CPC) and the adoption of an annular pipe (triple tube) improve the performance in terms of average bulk temperature, though not matching yet the surface reference collector in terms of efficiency.